Keterampilan Sosial Siswa Sekolah Dasar - Laesti Nurishlah; Mochammad Ramdan Samadi; Anisa Nurlaila; Iis Hasanah; Sabri (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
The research delves into the critical role of fostering social skills in elementary students, aiming to mold individual adept at navigating social environments. Utilizing a qualitative literature study method, it examines relevant data. The study emphasizes the vital contributions of educators and parents in honing students' social abilities, including fostering interpersonal relationships, honing communication skills, and facilitating conflict resolution. By fostering a supportive learning environment and providing ongoing parental guidance, students can develop the necessary social competencies to not only excel academically but also effectively engage in daily interactions. This holistic approach to social skill development ensures that students are well-equipped to succeed both in their academic pursuits and in their interpersonal relationships outside of the classroom.